"The Courageous Conference": British and American Newspaper Coverage of the 1915 Women's Peace Congress at The Hague. (5th October 2018) - Munro, Thomas
Abstract : From the outbreak of the First World War, newspapers in belligerent nations, such as Great Britain, and in neutral countries, such as the United States, discussed what the war might mean for the international order. The British and American public's engagement with ideas of international organisation was particularly evident in April 1915 when the Women's Peace Congress was held at The Hague. The overall purpose of the Congress may have been to protest the futility of war but what it produced was an alternative vision of international relations, one with both sexes and all the nations of the world equally represented. Relying on the negative stereotype of wartime newspapers, historians have argued that the contemporary press derided the Congress and the women involved. However, an examination of the British and American press demonstrates the extensive and positive coverage that a number of prominent newspapers gave the Congress. Newspaper reporting of the women's meeting at The Hague reveals the widespread contemporary acceptance of the Congress as another contribution to the vibrant debate about issues of peace and internationalism that had occurred since the war began.